1993
DOI: 10.1073/pnas.90.15.7069
|View full text |Cite
|
Sign up to set email alerts
|

Molecular cloning of the human kidney differentiation antigen gp160: human aminopeptidase A.

Abstract: ABSTRACTgp160 is a cell surface differentiation-related glycoprotein of 160 kDa expressed by epithelial cells of the glomerulus and proximal tubule cells of the human nephron but only by a subset of renal cell carcinomas (RCCs). We have reported that gp160 expression correlates with the resistance of cultured RCCs to the antiproliferative effects of a interferon, while lack of expression correlates with sensitivity to a interferon. In this study, we have purified gpl60 protein, obtained partial sequences of ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
76
0
2

Year Published

1996
1996
2015
2015

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 104 publications
(80 citation statements)
references
References 34 publications
2
76
0
2
Order By: Relevance
“…Aminopeptidase A is an ectopeptidase member of the peptidase family m1 proposed to play a role in the progression of cervical neoplasms (Fujimura et al, 2000). Interestingly, its expression in tissue culture correlates with resistance of renal carcinoma cells to the antiproliferative e ects of alpha-interferon (Nanus et al, 1993). Aminopeptidase A shows a 54% identity to aminopeptidase N, a gene recently found to promote invasion and to be expressed on proliferating endothelial cells undergoing angiogenesis (Pasqualini et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Aminopeptidase A is an ectopeptidase member of the peptidase family m1 proposed to play a role in the progression of cervical neoplasms (Fujimura et al, 2000). Interestingly, its expression in tissue culture correlates with resistance of renal carcinoma cells to the antiproliferative e ects of alpha-interferon (Nanus et al, 1993). Aminopeptidase A shows a 54% identity to aminopeptidase N, a gene recently found to promote invasion and to be expressed on proliferating endothelial cells undergoing angiogenesis (Pasqualini et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…extracellular domain (1)(2)(3) and is capable of cleaving N-terminal dipeptides with either L-proline or L-alanine at the penultimate position (2). CD26 activity is dependent on cell type and the microenvironment, factors that can influence its multiple biological roles (reviewed in Refs.…”
mentioning
confidence: 99%
“…Gluzincin aminopeptidases share the consensus HEXXH(X) 18 E zinc-binding motif essential for enzymatic activity (10). This growing family of mammalian zinccontaining aminopeptidase includes membrane-bound (P-LAP, aminopeptidase A, aminopeptidase N, and thyrotropin-releasing hormone degrading enzyme) (3,4,6,11,12), cytosolic (puromycin-sensitive aminopeptidase (PSA) and leukotriene A 4 hydrolase) (13,14), secretory (aminopeptidase B) (15), and ER resident (A-LAP/ERAP1) (9,16) proteins. Mutational analyses revealed that essential amino acid residues are well conserved among members of the family (17)(18)(19)(20).…”
mentioning
confidence: 99%